2018
DOI: 10.1186/s13054-018-2174-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of outcomes between vertical and transverse skin incisions in percutaneous tracheostomy for critically ill patients: a retrospective cohort study

Abstract: BackgroundPercutaneous tracheostomy (PT) is a common procedure in critical care medicine. No definite clinical practice guidelines recommended on the choice of the direction of skin incision, vertical or transverse for tracheostomy in critically ill patients. The objective of this retrospective study was to compare the outcomes associated with vertical and transverse skin incisions in patients undergoing PT.MethodsPatients who underwent PT between March 2011 and December 2015 in the intensive care unit (ICU) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…Surgical mistakes must be kept to an absolute minimum on the face, where existing folds and wrinkles [36] determine the logical direction of an incision or a fusiform skin excision [Figure 15]. For young patients, mimic movement of the face [Figure 16A and B] or a textbook on facial incisions [2,4,6-8] may serve as a guide for optimal directions.…”
Section: Face and Neckmentioning
confidence: 99%
See 2 more Smart Citations
“…Surgical mistakes must be kept to an absolute minimum on the face, where existing folds and wrinkles [36] determine the logical direction of an incision or a fusiform skin excision [Figure 15]. For young patients, mimic movement of the face [Figure 16A and B] or a textbook on facial incisions [2,4,6-8] may serve as a guide for optimal directions.…”
Section: Face and Neckmentioning
confidence: 99%
“…Incisions for tracheotomies [36] , thyroidectomies, or access to cervical discs should always be done higher up in the lower horizontal neck fold and clear of the jugulum to avoid hypertrophic scarring [5] [Figure 17A]. The "Kocher collar incision" dates back to the late 19th century [2] , when women were wearing high-necked dresses or heavy jewelry.…”
Section: Face and Neckmentioning
confidence: 99%
See 1 more Smart Citation
“…38 On the other hand, a retrospective study showed that transverse incision, compared to cephalo-caudal incision, resulted in less bleeding rates and tracheostomy site ulcers. 39 This study has several limitations. Firstly, the study was performed in Spanish, restricting participation to experts fluent in this language, which could reduce the external validity of our results.…”
Section: Discussionmentioning
confidence: 92%
“…It has been suggested that direct tracheal visualization and adequate dissection allows one to reduce both short‐term and long‐term complications 38 . On the other hand, a retrospective study showed that transverse incision, compared to cephalo‐caudal incision, resulted in less bleeding rates and tracheostomy site ulcers 39 …”
Section: Discussionmentioning
confidence: 99%